Effect of proteolitic enzymes with probiotic of lactic acid bacteria on characteristics of cow milk dadih - ., Miskiyah; Usmiati, S.; ., Mulyorini (Indonesian Animal Sciences Society, 2011)
Texture of dadih from cow milk tends to be soft, while dadih from buffalo milk have more compact and solid texture. Enzyme is one of food additives that may produce fermented products made from cow milk that has same charcteristic as dadihâs from buffalo milk. Lactic acid bacteria in fermented milk affect product characteristics. This study aimed to determine the effect of combination of enzyme and probiotic lactic acid bacteria on the characteristics of cows milk dadih. The study was aime designed using completely randomized design (CRD) with 9 treatments, A: renin 2 ppm + 3% Lactobacillus casei; B: renin 2 ppm + 3% B. longum); C: renin 2 ppm + 1.5% L. casei + 1.5% B. longum; D: crude extract of Mucor sp. 0.5 ppm + 3% L. casei; E: crude extract of Mucor sp. 0.5 ppm + 3% Brevibacterium longum; F: crude enzyme extract of Mucor sp. 0.5 ppm + 1.5% L. casei + 1.5% B. longum; G: papain 100 ppm + 3% L. casei); H: papain 100 ppm + 3% B. longum; and F: papain 100 ppm + 1.5% L. casei + 1.5% B. longum). Each treatment was repeated two times. Results showed that combination of renin 2 ppm with 3% of L. casei resulted in the best characteristics of cow milk dadih with viscosity 2278 cP; pH 5.63; titrable acidity 0.56%; moisture 75.03%; protein 6.80%; fat 3.35%; carbohydrate 13.21%; LAB total 6.90 x 1010 cfu/g; it also had a flavor, aroma, texture, and general acceptance that mostly preferred by panelists. Key Words: Dadih, Cow Milk, Enzyme, Lactobacillus casei, Bifidobacterium longum